Mitochondrial Encephalomyopathy (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Mitochondrial encephalomyopathy is a genetic disease caused by mutations in mitochondrial genes (mitochondrial DNA, mtDNA). Different symptoms occur due to mitochondrial or biochemical changes that occur in different tissues. Like many mitochondrial diseases, it occurs in many organs. Representative symptoms include myopathy, encephalopathy, lactic acidosis, and stroke-like episodes. In this article, we will talk about the causes, symptoms, diagnosis and treatment of Mitochondrial encephalomyopathy.